95.4k views
0 votes
Plz use Differential equation method to solve this:

LaTeX: y'=y+\frac{x}{y};\:\:y\left(0\right)=1

1 Answer

1 vote

Answer:

Explanation:

We have the differential equation
y' = y + (x)/(y) with initial conditions
y(0)=1.

First, notice that the equation can be rewritten as


y'-y =xy^(-1),

which is a Bernoulli equation. Once we have recognized the type of the equation we know how to continue. Recall that a Bernoulli equation has the general form


y'+p(x)y=q(x)y^n.

In this particular case we have
n=-1. This kind of equation is solved by the change of variable
z=y^(1-n). In our exercise we get
z=y^(1-(-1))=y^2. Now we take derivatives and get


z'=2yy' which es equivalent to
(z')/(2y)=y'.

Then, we substitute the value of
y' we have obtained in the original equation:


(z')/(2y)-y = xy^(-1).

The next step is to multiply the whole equation by
2y, in order to eliminate the denominator of
z'. Thus,


z' -2y^2=2x.

Recall that
y^2=z, then


z' -2z=2x.

This last equation is a linear equation, which has general solution


z(x) = \exp\left(-\int(-2)dx\right)\left(\int 2x \exp\left(\int(-2)dx + C\right)\right).

So, let us calculate the integral that appear in the formula:


\int(-2)dx = -2x


\int 2x e^(-2x)dx = -(\left(2x+1\right)e^(-2x))/(2).

Then, the solution for
z is


z(x) = e^(2x)\left(-(\left(2x+1\right)e^(-2x))/(2) + C\right) = -(\left(2x+1\right))/(2) + Ce^(2x).

Now, we return the change of variable:


(y(x))^2 =-(\left(2x+1\right))/(2) + Ce^(2x).

The last step is to find the value of the constant
C. In order to do this, substitute the initial value:


(y(0))^2 = 1 =(\left(2\cdot 0+1\right))/(2) + Ce^(2\cdot 0) = -(1)/(2) + C.

Thus, we have the equation


1=-(1)/(2) + C that gives
C=(3)/(2).

Therefore,


(y(x))^2 = -(\left(2x+1\right))/(2) + (3)/(2)e^(2x).

User Steven Noyes
by
4.3k points